2019
DOI: 10.3390/foods8050146
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of Streptococcus thermophilus Strains to Establish a Relation between Exopolysaccharide Characteristics and Gel Properties of Acidified Milk

Abstract: In situ produced extracellular polysaccharides (EPS) from lactic acid bacteria are generally known to affect the texture of fermented dairy products; however, the interplay between EPS and product properties is still poorly understood. The aim of this study was to establish a relationship between concentration and properties of EPS, and gel formation of milk analysed by noninvasive Multispeckle Diffusing Wave Spectroscopy. Twenty Streptococcus thermophilus strains were classified with respect to EPS concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 53 publications
2
19
0
Order By: Relevance
“…This fact is in agreement with the well-known statement that the capability to modify the viscosity of fermented milks is a strain and/or EPS-dependent feature [64]. It seems that LBIO28-fermented milks had a consistent structure that is more difficult to breakdown during shearing which, presumably, could be linked to the degree of ropiness of its EPS [65]. It seems that the role of this polymer is slowing the breakdown of the casein network through establishing strong EPS-protein interactions [66].…”
Section: Characterization Of Skim Milks Fermented With the Eps-producsupporting
confidence: 90%
“…This fact is in agreement with the well-known statement that the capability to modify the viscosity of fermented milks is a strain and/or EPS-dependent feature [64]. It seems that LBIO28-fermented milks had a consistent structure that is more difficult to breakdown during shearing which, presumably, could be linked to the degree of ropiness of its EPS [65]. It seems that the role of this polymer is slowing the breakdown of the casein network through establishing strong EPS-protein interactions [66].…”
Section: Characterization Of Skim Milks Fermented With the Eps-producsupporting
confidence: 90%
“…Thus, the progressing gelation process was demonstrated. Similar results were obtained by Surber et al [28], who observed that the gel properties of milk depend on the exopolysaccharide used, based on EI curves as a function of time. Rohart et al [27] used the MS-DWS method to evaluate the acid-induced gelation of skimmed milk.…”
Section: Rheological and Textural Characteristicssupporting
confidence: 89%
“…The isolation process of EPS is based on our previous study [ 15 ]. The EPS yield coefficient (mg/kg) was calculated according to the following formula: …”
Section: Methodsmentioning
confidence: 99%